Recent advances in the biology of tumour hypoxia with relevance to diagnostic practice and tissue‐based research. Issue 5 (18th March 2020) - Macklin, Philip S; Yamamoto, Atsushi; Browning, Lisa; Hofer, Monika; Adam, Julie; Pugh, Christopher W
Abstract: In this review article, we examine the importance of low levels of oxygen (hypoxia) in cancer biology. We provide a brief description of how mammalian cells sense oxygen. The hypoxia‐inducible factor (HIF) pathway is currently the best characterised oxygen‐sensing system, but recent work has revealed that mammals also use an oxygen‐sensing system found in plants to regulate the abundance of some proteins and peptides with an amino‐terminal cysteine residue. We discuss how the HIF pathway is affected during the growth of solid tumours, which develop in microenvironments with gradients of oxygen availability. We then introduce the concept of 'pseudohypoxia', a state of constitutive, oxygen‐independent HIF system activation that occurs due to oncogenic stimulation in a number of specific tumour types that are of immediate relevance to diagnostic histopathologists. We provide an overview of the different methods of quantifying tumour hypoxia, emphasising the importance of pre‐analytic factors in interpreting the results of tissue‐based studies. Finally, we review recent approaches to targeting hypoxia/HIF system activation for therapeutic benefit, the application of which may require knowledge of which hypoxia signalling components are being utilised by a given tumour. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.